New understandings of the genetic regulatory relationship between non-coding RNAs and m6A modification - Liu, Songtao; Xiang, Dayong (Frontiers in Genetics, 2023)
One of the most frequent epigenetic modifications of RNA in eukaryotes is N6 methyladenosine (m6A), which is mostly present in messenger RNAs. Through the influence of several RNA processing stages, m6A modification is a crucial approach for controlling gene expression, especially in cancer progression. It is universally acknowledged that numerous non-coding RNAs (ncRNAs), such as microRNAs, circular RNAs, long non-coding RNAs, and piRNAs, are also significantly affected by m6A modification, and the complex genetic regulatory relationship between m6A and ncRNAs plays a pivotal role in the development of cancer. The connection between m6A modifications and ncRNAs offers an opportunity to explore the oncogene potential regulatory mechanisms and suggests that m6A modifications and ncRNAs could be vital biomarkers for multiple cancers. In this review, we discuss the mechanisms of interaction between m6A methylation and ncRNAs in cancer, and we also summarize diagnostic and prognostic biomarkers for clinical cancer detection. Furthermore, our article includes some methodologies for identifying m6A sites when assessing biomarker potential.